Self-rated Health Among Saudi Women: Association with Morbidity, Lifestyle, and Psychosocial Factors - Hoda Jradi; Zuhaa Alharbi; Yasmeen Mohammad (Springer, 2018)
Self-rated health (SRH) is an essential global measure of general health and quality of life, and a predictor of the mortality and morbidity of populations. We assessed the SRH and identified associated factors among women in Riyadh, the capital of Saudi Arabia, using a cross-sectional survey conducted on a sample of women aged 18 years and older. Univariate and multivariate logistic regression analyses were conducted to identify factors that are significantly associated with SRH. Overall, 36.6% (n = 329) of participating women reported poor SRH. Higher body mass index (BMI), physical inactivity, greater number of morbidities, and reporting ill-being/likely depression were significantly associated with poor SRH. The findings from this study suggest that health status, lifestyle factors, and psychosocial conditions are associated with SRH in this population. Focusing on these factors suggests a turning point for public health policies and interventions to improve the health and quality of life of this group of women.